Agricultural trade liberalization : implications for Indian Ocean rim countries - Anderson, Kym (Centre for International Economic Studies, University of Adelaide, 2002)
"Professor Kym Anderson has produced an important study that looks at the benefits and costs associated with the liberalisation of agricultural trade among Indian Ocean Rim Association for Regional Cooperation (IOR-ARC) member countries."--p. iii.